Trajectories of local open government: An empirical investigation of managerial and political perceptions. Issue 4 (4th July 2021) - Schmidthuber, Lisa; Hilgers, Dennis
Abstract: 'Open government' refers to transparent, participative decision-making and platform-based citizen-government collaboration and has emerged as one paradigm at the local government level, in particular. However, substantial disparities exist in open government adoption among municipalities, and the empirical evidence on the determinants of open government adoption is sparse and mixed. This article considers open government adoption by integrating the resource- and knowledge-based views and decision-makers' open government willingness. We argue that the positive impacts of internal capacity depend on the municipal decision-makers' open government willingness. Using data from a survey conducted among local decision-makers, we investigate organizational ability to implement open government and decision-makers' preferences and adoption level. The findings indicate that organizational capacity is positively associated with open government. In addition, the effect of ability on adoption is partially mediated by leaders' perceptions that open government is a meaningful opportunity for the municipality.